In the public good : film censorship, the state and hegemony : a thesis submitted to the Department of Sociology, Massey University in partial fulfilment of the requirements for the degree of Master of Arts - Hill, Anthony Norwood (Massey University, 1983)
This thesis is a study of New Zealand State film censorship. It seeks to understand the nature and operation of film censorship as a State practice. In contrast to conventional approaches to censorship, this work seeks to understand the censorship of film in terms of Marxist theories of the State. It is argued that the process of film censorship is underpinned and explained by the hegemonic strategy that constitutes the New Zealand State's operation. The process and action of New Zealand film censorship is described through an ethnographic study and discussed in terms of this hegemonic strategy.
Keywords: Film censorship, New Zealand